Pseudoangiomatous stromal hyperplasia: an unsuspected cause of anisomasty. Issue 1 (1st January 2020) - Santanelli di Pompeo, Fabio; Sorotos, Michail; Passarelli, Francesca; Berrino, Valeria; Firmani, Guido; Winters, Harm; Paolini, Guido
Abstract: Breast asymmetry can be congenital or developmental, however a tumorous growth may be the cause of this condition after puberty. A 19-year-old female presented with a slowly developing breast asymmetry pre-operatively diagnosed as Pseudoangiomatous Stromal Hyperplasia (PASH). The patient underwent tumour excision with breast gland remodelling. Postoperative course was uneventful.